Methodological components of the modernization of fleet of aircraft in modern terms - Самков, О.В. (Proceedings of National Aviation University (archive), 2008)
In the article methodological constituents are examined in relation to the decision of problem tasks from modernization of parks of aviation technique in the conditio ns of insufficiency and vagueness of providing resourse.